Wide QRS tachycardia associated with multiple accessory pathways in a patient with Wolff–Parkinson–White syndrome. Issue 6 (December 2019) - Nakamura, Toshihiro; Kanda, Gaku; Sasaki, Yoshihiro; Noda, Rei; Hiranuma, Noritoshi; Sumimoto, Keiko; Fujii, Takashi
Abstract: The electrocardiogram of a 14-year-old boy with recurrent palpitation showed a wide QRS regular tachycardia with a right bundle branch block and right-axis deviation of 226 beats per minute. Verapamil infusion terminated the tachycardia after a few minutes. Electrophysiological study revealed that this tachycardia was considered as a reentrant tachycardia associated with the anterograde left posterior accessory pathway (AP) and retrograde right septal AP. Radiofrequency application was performed and eliminated both APs, and there was no recurrence of wide QRS tachycardia. <Learning objective: Wide QRS tachycardia in young patients with no organic heart disease includes an uncommon supraventricular tachycardia. Wide QRS tachycardia utilizing different dual accessory pathways (APs) has rarely been reported. The refractory periods of the APs were shorter than that of atrioventricular node, and the shortest refractory period on anterograde and retrograde conduction was recorded at the left posterior AP and the right septal AP respectively. These findings were to be felt most consistent with the mechanism of maintaining an atrioventricular reentrant tachycardia with multiple APs.>